Prevalence of Self-Reported Erectile Dysfunction Among Urological Cases in Turkish Men - Bayraktar, Zeki; Atun, Ihsan (Urology Journal, 2011)
Purpose: To determine the prevalence of self-reported erectile dysfunction (ED) among urological cases in Turkish men. Materials and Methods: Between January 2007 and January 2011, the diagnoses of 9780 men over 18 years old that presented to our urology polyclinic were reviewed. The 10 diseases with the highest frequency, the rate of the disease, and the intra-group ranking were determined in 18 to 39, ≥ 40-year-old, and in total. The rate of ED among urological cases was considered to be the self-reported ED prevalence. The findings were evaluated using the population-based (Turkey) ED prevalence found in the literature. Also, the prevalence of benign prostatic hyperplasia (BPH) was evaluated in the Turkish population. This evaluation compared the ED and BPH prevalence. Results: The prevalence of ED (self-reported ED) was 1.9%, 8.2%, and 4.8% in the age groups of 18 to 39, ≥ 40-years, and total, respectively. The intra-group ranking of ED was 8th, 3rd, and 8th in the aforementioned groups, respectively. The most frequent disease was BPH in total and ≥ 40-year-old groups. The ratio of patients with BPH to ED was 6.1 (BPH/ED: 2250/366). The prevalence of ED (self-reported ED) as well as BPH significantly increased with age (P < .001 and P < .001, respectively). Conclusion: The prevalence of ED in urological cases is relatively lower than expected. There is a discrepancy between the self-reported ED prevalence in urological cases and population-based ED prevalence.